Essential Study Skills : The Complete Guide to Success at University - Burns, Tom (SAGE Publications, Ltd. (UK), 2022)
"If you′re looking to be that top student, this book is a must!" – five-star student review Packed with study tips, activities, templates and quotes from students, this is your essential guide to university, showing you step-by-step how to study effectively and make the best of your time at university. Whether you are going to university straight from school, as a mature, or as an overseas student studying in the UK for the first time, you′ll find out how to: Sail through those tricky first weeks Get the most out of lectures by understanding how you learn Learn techniques for academic writing and research Effectively work with others in groups, seminars and workshops Write assignments and pass exams with flying colours Build your CV and plan your next steps after graduation. New to this edition is content on how to thrive at university, learn and research digitally, and how to develop your employability skills. Student Success is a series of essential guides for students of all levels. From how to think critically and write great essays to boosting your employability and managing your wellbeing, the Student Success series helps you study smarter and get the best from your time at university.